DETERMINASI LOYALITAS KONSUMEN PADA MASYARAKAT MUSLIM JABODETABEK DENGAN PERCEIVED VALUE SEBAGAI VARIABEL MEDIASI - Winna Syahzarni (2023)
Consumer loyalty to a product is influenced by many factors, such as price, product quality, and design. In addition, perceived value that is well managed by the company can also achieve various business goals, such as increasing consumer loyalty. This research is a quantitative research that aims to determine the effect of halal labels, prices, and product quality on consumer loyalty with perceived value as a mediating variable. This study used primary data obtained through distributing questionnaires which were responded to by 115 Muslim consumers using Indonesian skincare in Jabodetabek. Selection of the sample in this study using purposive sampling. The data analysis technique used is Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results of this study indicate that the variable halal label and price have no significant effect on consumer loyalty, while product quality and perceived value have a significant effect on consumer loyalty. In the mediating variable, the halal label has no significant effect on perceived value. while price and product quality have a significant effect on perceived value. In the indirect effect, the halal label does not have a significant effect on consumer loyalty through perceived value as mediation, while price and product quality have a significant effect on consumer loyalty mediated by perceived value partially.